POLÍTICA E GÊNERO ENTRE VOZES E LENTES DO PODER JUDICIÁRIO: PRODUÇÃO DE DISCURSOS E IMAGENS DE MULHERES POLÍTICAS EM PEÇAS PUBLICITÁRIAS DO TSE (2014 E 2016). - SANTOS, Michelle Aranha Coelho dos (2019)
Analysis of discourse’s production and images of political women in Judiciary’s propagandas that circulated in TV in the years 2014 and 2016, marked presidential and municipal, respectively. It begins with the studies of the philosopher Michel Foucault on the constitution of the subjects and the production of discourse, through mechanisms of power that allow the new actions of the processes of subjectivation, when selecting some discourses making us as affirmative, while silencing and interdicting others. The theme is studied in the light of the French Discourse Analysis (AD), especially in its third phase, marked by foucaultian reflexes (2015a, 2015b, 2014, 2013a, 2013b, 2017a, 2017b, 2010a, 2010b, 2004, 1984, 1982) in conjunction with reflections and concepts (DUBOIS, 2004; GERBASE, 2012), because of the nature audiovisual of the corpus. There is also mobilization of reflections from Historical Semiology, since it allows us to look at the object of the AD as an object, especially semiological and historical dimension (COURTINE, 2011; BERNARDES & SARGENTINI, 2014). For the understanding of Gender issues, post-structuralist feminist theories will be bases for this study (BUTLER, 2017a, 2017b, 2001; LOURO, 2014), that problematize the woman object, taking it in its diversity and plurality. The methodology is qualitative and procedurally based on the analysis of three propagandas transmitted in the television business, which emerged from the Women in Politics campaign of the Supreme Electoral Tribunal (TSE) in 2014 and followed in 2016 as part of the Campaign Equality in politics. It seeks to observe how women are being represented in propagandas of the Superior Electoral Tribunal and Brazilian Electoral Justice, especially which images are being produced there through certain mechanisms and power relations, and also, as the discourses circulate there to constitute the object of which it is spoken. Thus, the general objective of this work is to understand the production of the subject-woman-politics in propagandas of the Judiciary as a discursive process that takes place through norms, disciplines, visibility and invisibility. In this investigation, it will be tried to discuss to what disciplines the "women" must obey to become political subjects, and that statements are put to exercise this discipline in publicity pieces of this organ. It is also thought that these institutions do not envisage senses in the visibilization of certain types of women, recovering a discursive memory of the common sense media that privileges certain bodies, when conferring the false illusion of visibility. In this sense, it is observed that in the name of a supposed democracy, justice produces a subject that will be represented.